Post-translational Modifications and Protein Quality Control in Motor Neuron and Polyglutamine Diseases - Sambataro, Fabio; Pennuto, Maria (Frontiers in Molecular Neuroscience, 2017)
Neurodegenerative diseases, including motor neuron and polyglutamine (polyQ) diseases, are a broad class of neurological disorders. These diseases are characterized by neuronal dysfunction and death, and by the accumulation of toxic aggregation-prone proteins in the forms of inclusions and micro-aggregates. Protein quality control is a cellular mechanism to reduce the burden of accumulation of misfolded proteins, a function that results from the coordinated actions of chaperones and degradation systems, such as the ubiquitin-proteasome system (UPS) and autophagy-lysosomal degradation system. The rate of turnover, aggregation and degradation of the disease-causing proteins is modulated by post-translational modifications (PTMs), such as phosphorylation, arginine methylation, palmitoylation, acetylation, SUMOylation, ubiquitination, and proteolytic cleavage. Here, we describe how PTMs of proteins linked to motor neuron and polyQ diseases can either enhance or suppress protein quality control check and protein aggregation and degradation. The identification of molecular strategies targeting these modifications may offer novel avenues for the treatment of these still incurable diseases.